2018
DOI: 10.1021/acs.chemmater.7b03818
|View full text |Cite
|
Sign up to set email alerts
|

Area-Selective Atomic Layer Deposition of Metal Oxides on Noble Metals through Catalytic Oxygen Activation

Abstract: Area-selective atomic layer deposition (ALD) is envisioned to play a key role in next-generation semiconductor processing and can also provide new opportunities in the field of catalysis. In this work, we developed an approach for the area-selective deposition of metal oxides on noble metals. Using O2 gas as co-reactant, area-selective ALD has been achieved by relying on the catalytic dissociation of the oxygen molecules on the noble metal surface, while no deposition takes place on inert surfaces that do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 64 publications
2
101
0
Order By: Relevance
“…Ultrathin metal oxides by ALD have been applied to encapsulate the supported nanoparticles and improve the size stability of nanoparticle catalysts 35,36 . In order to minimize additional electrocatalytic effects from ALD overcoating layer, we chose the relatively inert Al 2 O 3 rather than the typical transition metal oxide promotors (e.g., Co 3 O 4 37 , MnO 38 , Fe 2 O 3 39 , and MoO 3 40 ). ALD of a thin Al 2 O 3 layer was carried out to stabilize the ultrasmall PtP 2 NCs on a commercial carbon support by alternately exposing the sample to cycles of trimethylaluminum (TMA) and water at 175°C (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Ultrathin metal oxides by ALD have been applied to encapsulate the supported nanoparticles and improve the size stability of nanoparticle catalysts 35,36 . In order to minimize additional electrocatalytic effects from ALD overcoating layer, we chose the relatively inert Al 2 O 3 rather than the typical transition metal oxide promotors (e.g., Co 3 O 4 37 , MnO 38 , Fe 2 O 3 39 , and MoO 3 40 ). ALD of a thin Al 2 O 3 layer was carried out to stabilize the ultrasmall PtP 2 NCs on a commercial carbon support by alternately exposing the sample to cycles of trimethylaluminum (TMA) and water at 175°C (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Second, the oxygen uptake phenomenon may be related to that of a recent report of Fe 2 O 3 ALD on Pt surfaces where it was hypothesized that oxygen was transported through the film. [ 68 ] In the study by Singh et al, it was observed that when performed on platinum substrates, iron oxide ALD could be achieved using tert ‐butylferrocene and molecular oxygen gas, obviating the need for ozone. While O 2 was not reactive enough to react with the iron precursor at moderate temperatures, it was hypothesized that the oxygen species were able to migrate through the film to the underlying platinum substrate where it was dissociated into reactive oxygen atoms to participate in the ALD reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Pt could selectively initiate its growth on Pd to form a core-shell structure exclusively (shown in Fig. 4a) [58][59][60].…”
Section: Conformal Coating On Particlesmentioning
confidence: 99%